The Influence of Cellupract AS100 Enzyme Treathment to Ricebran and Cotton Seed Mealon Chemical Composition, Energy Content and In Vitro Digestibilityt - M Bata; S.N.O. Suwandyastuti; S. Chakeredza; G. Thinggaard; U ter Meulen (Jurnal Sain Veteriner, 2004)
.